THE EFFECTS OF INAPPROPRIATE USE OF BENZODIAZEPINE IN GERIATRICS: AN ASSESSMENT BASED ON BEER’S PARAMETERS (REMUNOM, 2024)
Physiological changes with aging, due to the impairment of renal and hepatic function, affect the metabolism and elimination of drugs, increasing the risk of adverse effects. The growing prevalence of chronic diseases among the elderly contributes to high medication consumption, particularly the use of benzodiazepines for treating anxiety and insomnia, which show efficacy in short-term treatments. However, the prolonged use of these medications, especially among older adults, raises significant concerns. Studies indicate that despite their effectiveness, benzodiazepines can lead to dependence and a range of long-term adverse effects, such as drowsiness, fatigue, confusion, headaches, anxiety, lethargy, ataxia, postural hypotension, retrograde amnesia, accidents, tolerance, dependence, and an increased frequency of falls. The Beers Criteria aim to enhance medication therapy by prioritizing patient-centered decisions and considering what is most important for the older individual, with the goal of optimizing health and minimizing unnecessary risks.